2000
DOI: 10.1097/00004872-200018010-00016
|View full text |Cite
|
Sign up to set email alerts
|

Development of different phenotypes of hypertensive heart failure

Abstract: These two different models of overt heart failure may be useful as models of isolated diastolic heart failure and systolic heart failure based on the same hypertensive heart disease, respectively, and may contribute to discrimination of the mechanisms of the development of the two different phenotypes of heart failure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
29
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(34 citation statements)
references
References 34 publications
2
29
0
Order By: Relevance
“…1D). At 18 weeks, E/A ratio in HS rats approached values in NS rats (1.46±0.17 vs. 1.60±0.08, p=0.27) consistent with pseudo-normalization of E/A ratio as seen in the progression of diastolic dysfunction 22, 41 (Fig. 1D).…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“…1D). At 18 weeks, E/A ratio in HS rats approached values in NS rats (1.46±0.17 vs. 1.60±0.08, p=0.27) consistent with pseudo-normalization of E/A ratio as seen in the progression of diastolic dysfunction 22, 41 (Fig. 1D).…”
Section: Resultssupporting
confidence: 74%
“…1A. In brief, male 7 week-old DSS rats (Charles River Laboratories, MA) underwent baseline transthoracic echocardiography and were then randomly assigned to a high-salt (HS) diet (AIN-76A + 8% NaCl with irradiation, Research Diets, NJ) to induce HFpEF (n=38), 21, 22 or to a normal-salt (NS) diet (AIN-76A [0.3 % NaCl] with irradiation) as controls (n=13). Feeding was continued ad libitum until rats reached the experimental endpoints at 14–18 weeks old.…”
Section: Methodsmentioning
confidence: 99%
“…Additional possible mechanistic explanations for the dietary-induced changes in cardiac AT 1 R and MR include changes in cardiac filling or BP. Though we did not assess the effect of dietary sodium on cardiac filling in our study, other investigators (Doi et al 2000) have demonstrated that a very high 3 . 2% sodium (8% NaCl) diet for 6 weeks did not alter left ventricular diastolic filling compared to rodents on a low 0 .…”
Section: Discussionmentioning
confidence: 79%
“…The DSS model has been reproducibly used to investigate cardiac hypertrophy, diastolic dysfunction, and transition to heart failure (9,16). Therapies shown to attenuate cardiac dysfunction in this model (17,18) ameliorate comparable cardiac abnormalities in humans (19).…”
Section: Discussionmentioning
confidence: 99%